DIDACTIC CONDITIONS OF USING VISUAL MODELING SOFTWARE TOOLS IN MODELING HYDROTECHNIC INSTALLATIONS - Shaynazarov Ravshan Mamayusubovich (The Conference Hub, 2025)
This article presents solutions for automating the activities of organizations involved in the construction and operation of hydraulic structures by applying modern modeling technologies in their design. It highlights 3D design solutions for hydraulic structures developed by IT companies using modern engineering software. In addition, the article discusses the best software for modeling hydraulic structures, the technologies used in such software, and the necessity of learning how to work with modeling programs for hydraulic engineering. The paper also reviews some of the best options for learning how to create 3D models both for video games and professional engineering projects, and provides an overview of the work conducted by researchers who have studied these issues.
Keywords: Visualization, converting into visual representation, Infographics, engineering graphics, 3D technologies, SketchUp, Blender.